2020
DOI: 10.1097/cce.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High-Flow Nasal Oxygen in the ICU as a First-Line Therapy for Acute Hypoxemic Respiratory Failure Secondary to Coronavirus Disease 2019

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…Search terms yielded 84 articles relating to a total of 13 140 patients after exclusion of duplicates, and after screening titles, abstracts, and full text for relevance specifically to outcomes with the use of NIRS in patients with COVID-19 ( appendix p 1 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Search terms yielded 84 articles relating to a total of 13 140 patients after exclusion of duplicates, and after screening titles, abstracts, and full text for relevance specifically to outcomes with the use of NIRS in patients with COVID-19 ( appendix p 1 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
“…Other than two multicentre RCTs from Italy and the UK, 38 , 95 22 prospective and 61 retrospective observational studies were identified, reporting a median of 71 patients (IQR 40–127) per study. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 HFNO also increases carbon dioxide excretion and diminishes work of breathing. 8 , 11 , 12 , 13 , 14 During the COVID-19 pandemic, HFNO has been widely used to support patients with bilateral pulmonary infiltrates and hypoxaemia due to SARS-CoV-2 pneumonia, 15 , 16 , 17 including those managed in resource-limited settings 18 and patients with severe COVID-19-associated ARDS managed in the prone position, 19 who typically meet all other Berlin diagnostic criteria for ARDS other than the requirement for invasive or non-invasive mechanical ventilation.
Figure Proposed expansion of the Berlin definition of ARDS ARDS=acute respiratory distress syndrome.
…”
Section: Patients Receiving Hfnomentioning
confidence: 99%
“…Reports of first-line use of highflow nasal cannula oxygen has not demonstrated inferior outcomes, nor has the timing of intubation, suggesting a significant portion of patients could benefit from a trial of therapy and eventually avoid intubation. [11][12][13][14] Other therapies, such as systemic corticosteroids, confer a mortality benefit in those patients with COVID-19 who require oxygen or mechanical ventilation, but their impact on the progression of respiratory failure and need for intubation are undetermined.…”
mentioning
confidence: 99%